Utilizing Sales Data to Optimize Digital Marketing Strategies for Beauty Products in Padangsidimpuan City - Rosi Ramayanti; Ihdi Syahputra (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
This study presents a data-driven framework for optimizing digital marketing strategies of beauty products in Padangsidimpuan. Motivated by the dominance of the Y.O.U brand (47.8% portfolio share) and an average store/BA target achievement rate of 43.7% with a 55.5% revenue gap, the research aims to integrate product portfolio analytics (price, margin, segmentation, brand) with sales performance analysis (target vs. actual). A quantitative descriptive approach was employed using secondary internal data—1,297 SKUs with sell-in/out prices and margin metrics, and monthly targets and achievements for 27 stores and 25 beauty advisors (August 2025)—supported by library research on digital marketing literature. Data analysis included descriptive statistics, price segmentation, brand distribution, margin analysis by segment, and performance gap assessment. Findings reveal a portfolio concentration in the mid-price segment (30k–60k, 38.6%) with an average margin of 31.3%, while only 14.2% of SKUs exceed 40% margin. The average achievement rate of 43.7% (range 0–91.1%) underscores the need for targeted digital interventions. The proposed framework prioritizes high-margin SKUs for paid media, SEO for mid-range products, cross-category bundling, live streaming, personalized content, and RACE-based KPI governance. Implementation is expected to close revenue gaps and raise the achievement rate above 60% within 1–2 quarters. The framework is adaptable to similar regional markets. Keywords: sales data, digital marketing, price segmentation, beauty products, RACE framework.